Güncel Bakış Açısıyla Psikolojiye Giriş - Yazıcı, Zeynep; Çimen, Fatmanur; Aktu, Yahya; Epli, Hatice; Çolak Turan, Tuğba Seda; Ulaş, Sümeyye; Turgut, Özden; Ay, İsmail; Alkım Arı, Fikriye; Fırat, Sunay; Erk, Mehmet Aykut; Tatlı, Eda; et al. (2023)
-